No horizontal numerical mapping in a culture with mixed-reading habits - Rashidi-Ranjbar, Neda; Goudarzvand, Mahdi; Jahangiri, Sorour; Brugger, Peter; Loetscher, Tobias (Frontiers in Human Neuroscience, 2014)
Reading habits are thought to play an important role in the emergence of cultural differences in visuo-spatial and numerical tasks. Left-to-right readers show a slight visuo-spatial bias to the left side of space and automatically associate small numbers to the left and larger numbers to the right side of space, respectively. A paradigm that demonstrated an automatic spatial-numerical association involved the generation of random numbers while participants performed lateral head turns. That is, Westerners have been shown to produce more small numbers when the head was turned to the left compared to the right side. We here employed the head turning/random number generation paradigm and a line bisection task to a group of 34 Iranians in their home country. In the participants’ native language (Farsi) text is read from right-to-left, but numbers are read from left-to-right. If the reading direction for text determines the layout of spatial-numerical mappings we expected to find more small numbers after right than left head turns. Yet, the generation of small or large numbers was not modulated by lateral head turns and the Iranians showed therefore no association of numbers with space. There was, however, a significant rightward shift in the line bisection task. Thus, while the current results tie in with the idea that reading habits for text play an important role for cultural differences observed in visuo-spatial tasks, our data also imply that these habits on their own are not strong enough to induce significant horizontal spatial-numerical associations. In agreement with previous suggestions we assume that for the emergence of horizontal spatial mappings a congruency between reading habits for words and numbers is required.